Acid‐Catalyzed Hydration of Alkynes in Aqueous Microemulsions. Issue 3 (11th February 2013) - Nairoukh, Zackaria; Avnir, David; Blum, Jochanan
<x xml:space="preserve">Abstract</x> Terminal aromatic alkynes are converted rapidly into ketones in a regioselective manner by treatment of their microemulsions with 0.33 M mineral acid between 80 and 140 °C. Internal and aliphatic acetylenes are likewise hydrated, but require longer reaction periods. The products are easily isolated from the reaction mixtures by phase separation. Replacement of H2O by D2O leads to the formation of trideuteriomethyl ketones.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>